Aspirasi pekerjaan pelajar kejuruteraan sekolah menengah teknik - Kasa, Zakaria; Bakar, Ab. Rahim (Universiti Putra Malaysia Press, 2004)
Career aspiration is an important aspect in a person's life that can influence his or her career development. Career aspirations can become a motivating force to school students to get involved in certain kinds of jobs. A descriptive study was conducted to identify the career aspirations of engineering students in the secondary technical schools in Peninsular Malaysia. A total of 1,123 Form Four students was chosen as research sample. Questionnaires were used to collect the data. The findings showed that many female students were enrolled in the fields of civil and construction engineering, whereas many male students were enrolled in the fields of electrical and mechanical engineering. A majority of the respondents said that they had chosen their fields of study because of their interests. Though even the respondents enrolled in the fields of engineering, only one half of them had the ambition to become engineers, whereas the others had chosen other kinds of jobs besides engineers. As a result, it was suggested that efforts should be made to attract more students to be interested in becoming engineers, especially among those enrolled in the field of engineering. This could be done by exposing them to various kinds of jobs that were related to their fields of study.